MALFEASANCE, ADMINISTRATIVE JUSTICE AND THE RIGHT OF ACCESS TO HEALTH-CARE SERVICES: AN ASSESSMENT OF MEC for Health v Kirkland Investment (Pty) Ltd 2014 (5) BCLR 547 (CC) - Karthy Govender (Obiter, 2015)
This case will reflect on some of the decisions made by senior civil servants in the discharge of important statutory powers, and will argue that improper decisions retard our growth as a democracy. The Kirkland case demonstrates that the failure to act in a just administrative manner will also hinder the progressive realization of socio-economic rights, such as the right of access to health care. We appear to be faring poorly on two of the three factors on Mureinik’s watch list and this must give cause for concern.